Sex-disparities in pediatric and young adult patients with psoriasis treated with biologics: differences in adverse events and disease activity - Malak Al-Gawahiri; Liana Barenbrug; Ewald M. Bronkhorst; Elke M. G. J. de Jong; Juul M. P. A. van den Reek; Marieke M. B. Seyger (Journal of Dermatological Treatment)
Introduction Sex-differences in biological treatment outcomes in adult patients with psoriasis are well known. Potential sex-differences in a real-world cohort of pediatric and young adult patients with psoriasis using biologics were investigated in this study.Methods Data on pediatric (<18 years) and young adult (≥18 to ≤30 years) patients were obtained from the prospective, daily practice, ChildCAPTURE and BioCAPTURE registries. Drug survival and adverse event rates were compared between sexes. Confounder-corrected linear mixed models were used to compare Psoriasis Area and Severity Index (PASI) and (Children’s) Dermatology Life Quality Index ((C)DLQI) scores between sexes.Results We included 117 pediatric (65 females) and 243 young adult (124 females) patients on biologics (753.4 observation years). Young adult males had a significantly higher PASI at biologic initiation compared to females, with the same trend for pediatric patients. A higher adverse event rate was observed in females compared to males in both pediatric and young adult patients. Drug survival, PASI and (C)DLQI course during the first treatment year, were comparable between pediatric and young adult females and males.Conclusion Awareness on sex-differences (start PASI and adverse event rates) in pediatric and young adult patients with psoriasis is important for timely initiation and adjustment of appropriate treatment.